2005
DOI: 10.2298/fuace0502173t
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion survey as a form of public participation in the implementation of water framework directive: Case study - Leskovac field irrigation

Abstract: Abstract. The adoption of the Water Framework Directive is a turning point in the development of European water resources management. For the first time in the history

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Following interview accounts, citizens start caring about such issues once the policies are implementede.g. once their house is due to be demolished because of the construction of a dike (for comparable experiences, see Slavíková & Jílková, 20 2011;Trajekovic, Kolakovic, & Ignjatovic, 2005). Also, one should ask to what extent citizens can get involved when they have only one chance to attend a meeting relating to their (sub)river basin, and how a citizen's voice makes it all the way up to the actual decision making process.…”
Section: By 2008 Citizens (Or To Use the Eu Working Group On Publicmentioning
confidence: 99%
“…Following interview accounts, citizens start caring about such issues once the policies are implementede.g. once their house is due to be demolished because of the construction of a dike (for comparable experiences, see Slavíková & Jílková, 20 2011;Trajekovic, Kolakovic, & Ignjatovic, 2005). Also, one should ask to what extent citizens can get involved when they have only one chance to attend a meeting relating to their (sub)river basin, and how a citizen's voice makes it all the way up to the actual decision making process.…”
Section: By 2008 Citizens (Or To Use the Eu Working Group On Publicmentioning
confidence: 99%
“…For instance, in certain areas of Serbia, survey questionnaires were sent to inhabitants. Yet, researchers are uncertain of the success of this approach to public participation, which may partly have to do with survey respondents' disinterest in the wider goals of the WFD (Trajekovic et al ., ). Another example comes from a study on public participation in Germany (Kampa et al ., ).…”
Section: Case Study: Public Participation In the European Water Framementioning
confidence: 97%
“…The irrigation represents the measure that gives the most efficient results against drought. In [8], the public opinion survey was conducted in Leskovac municipality, and showed that a great number of farmers comprehends the great importance of irrigation, but a negligible part of the respondents was accepted the fact that the construction of the system inevitably enables the changes in crop structure, irrigation methods and water price. Also, 89% of the respondents mostly used the underground water, and 66% of farmers said that they were satisfied only with pumps.…”
Section: Figure 1 Drought-based Regionalization In Serbia ([7])mentioning
confidence: 99%